Use the force: deformation correction in robotic 3D ultrasound - Virga, Salvatore; Goebl, Rudiger; Baust, Maximilian; Navab, Nassir; Hennersperger, Christoph (International Journal of Computer Assisted Radiology and Surgery, 2018)
Purpose: Ultrasound acquisitions are typically affected by deformations due to the pressure applied onto the contact surface. While a certain amount of pressure is necessary to ensure good acoustic coupling and visibility of the anatomy under examination, the caused deformations hinder accurate localization and geometric analysis of anatomical structures. These complications have even greater impact in case of 3D ultrasound scans as they limit the correct reconstruction of acquired volumes. Methods: In this work, we propose a method to estimate and correct the induced deformation based solely on the tracked ultrasound images and information about the applied force. This is achieved by modeling estimated displacement fields of individual image sequences using the measured force information. By representing the computed displacement fields using a graph-based approach, we are able to recover a deformation-less 3D volume. Results: Validation is performed on 30 in vivo human datasets acquired using a robotic ultrasound framework. Compared to ground truth, the presented deformation correction shows errors of 3.39±1.86mm for an applied force of 5 N at a penetration depth of 55 mm. Conclusion: The proposed technique allows for the correction of deformations induced by the transducer pressure in entire 3D ultrasound volumes. Our technique does not require biomechanical models, patient-specific assumptions or information about the tissue properties; it can be employed based on the information from readily available robotic ultrasound platforms.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Compounding; Deformation correction; Inpainting; Robotic ultrasound